ANALISIS TEKNIK PERKEMBANGAN MURID DI SEKOLAH DASAR GMIT 33 MORU 1 - Penina Maruli; Reni Sriyanti Besi, Muhammad Songge, Mita Laana, Yessy Mata, Petrus Mau Tellu Dony (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Elementary School. Data analysis used qualitative methods. To understand elementary school student development, the data used in this study was qualitative. The method used in this study was interviews. These interviews were conducted at GMIT 33 MORU 1 Elementary School, Alor Barad Daya District, Alor Regency. The results oftheseinterviews indicate: (1). Types of data used in elementary schools, (2). Data needed in elementary schools, (3) Appropriate guidance planning, (4). Monitoring guidance in elementary schools, (5). Student needs in elementary schools, (6.) How teachers can demonstrate appropriate forms of service in elementary schools, (7). Types of data about students.